Pengembangan Callytikya Berbasis Canva dan Genially Sebagai Media Pembelajaran IPAS di Kelas V Sekolah Dasar - Dinata, Nurfina Azmia; Hidayat, Taufik; Makmun; Mustamiroh (Tunas: Jurnal Penelitian Pendidikan Dasar, 2025)
This research is motivated by the lack of variety in the use of digital-based learning media in the classroom. The use of learning media in the classroom is still dominated by books and loaded in the form of text, especially in IPAS subjects so that students tend to be passive and less active in learning because the learning media used are less interesting and look less real. This study aims to explain the media development process, media feasibility, and effectiveness of the media. This research uses the Research and Development method with the ADDIE model which consists of 5 procedures namely Analyze, Design, Development, Implementation and Evaluation. The research subjects were 23 fifth grade students of Al-Quds Samarinda Islamic Elementary School and the object was Callytikya learning media that had been developed. Callytikya is the name of the product developed by the researcher which stands for Canva Genially Geographical Characteristics of Indonesian Regions. Data collection techniques use observation, interviews, and questionnaires. The data analysis technique uses quantitative descriptive data analysis. The research findings are as follows: (1) produce a product called Callytikya, namely learning media based on Canva and Genially; (2) Callytikya learning media has met the eligibility criteria (eligibility of material experts 88%, media experts 92%, and linguists 90%) with a very feasible category; (3) Callytikya learning media has met the criteria.